Aortic root enlargement: Just do it. Issue 8 (28th May 2022) - Yousef, Sarah; Sultan, Ibrahim
Abstract: Aortic root enlargement (ARE) can be an important adjunct for aortic valve replacement (AVR) in patients with small annuli, but incremental morbidity of this procedure is not well understood.